Perinatal intimate partner violence and breastfeeding practices: A systematic review and meta-analysis protocol - Zelalem Nigussie Azene; Catherine MacPhail; Lisa Gaye Smithers (PLoS ONE, 2025)
Background Intimate partner violence increases the risk of detrimental health, behaviors and psychological issues in mothers, affecting infant nutrition and development. However, the potential effects of maternal exposure to intimate partner violence on breastfeeding practices are understudied, and the results of individual studies are inconsistent and conflicting. The aims of this systematic review and meta-analysis are therefore to 1) estimate the prevalence of perinatal intimate partner violence and, 2) examine the relationship between perinatal intimate partner violence and breastfeeding outcomes. Methods and analysis This systematic review and meta-analysis will investigate the association between perinatal intimate partner violence and breastfeeding outcomes, including early initiation within 1 hour after giving birth, exclusive breastfeeding under six months, and continued breastfeeding at two years or beyond. Comprehensive searches will be conducted in PsycInfo, Scopus, Web of Science, Medline, Cochrane, JBI EBP, CINAHL, Informit, and PubMed electronic databases. Data extraction will be performed independently by two reviewers, with discrepancies resolved by a third reviewer. Statistical analysis will be conducted using STATA/SE version 17, employing random-effects models to calculate pooled effect sizes and assess heterogeneity with I2 and Chi-square tests. Subgroup analyses and meta-regression will explore potential sources of heterogeneity. Discussion and conclusion Evidence suggests that intimate partner violence is linked to poor breastfeeding outcomes. This systematic review and meta-analysis will update, compile, and critically review the evidence of the role of intimate partner violence on breastfeeding outcomes. This systematic review and meta-analysis will also inform effective strategies and interventions to support breastfeeding among IPV-affected women, thereby enhancing maternal and child health. Ethics and dissemination As this review and meta-analysis involves secondary analysis of existing data, ethical approval is not required. Findings will be disseminated through peer-reviewed publications and scientific conferences, aiming to inform strategies to support breastfeeding among women affected by intimate partner violence. Study registration This protocol is registered with the International Prospective Register of Systematic Reviews (PROSPERO), registration number CRD42024555048.